2021
DOI: 10.1186/s12913-021-07071-2
|View full text |Cite
|
Sign up to set email alerts
|

Capacity development and safety measures for health care workers exposed to COVID-19 in Bangladesh

Abstract: Background The safety of health care workers (HCWs) in Bangladesh and the factors associated with getting COVID-19 have been infrequently studied. The aim of this study was to address this gap by assessing the capacity development and safety measures of HCWs in Bangladesh who have been exposed to COVID-19 and by identifying the factors associated with respondents’ self-reported participation in capacity development trainings and their safety practices. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The possible explanation is that those with high monthly income may be able to acquire additional materials needed to establish themselves in hygienic conditions [such as personal protective equipment, hand sanitizer] and acquire extra cooking training, including food safety practices [34]. In Bangladesh, hospital authorities generally provide PPE to staff; however, the quality and adequacy of PPE can be a concern, especially during the crisis period [56]. A recent study reported that nearly half of the respondents [50%] claimed that there was an inadequate supply of PPE for hospitals and healthcare workers [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible explanation is that those with high monthly income may be able to acquire additional materials needed to establish themselves in hygienic conditions [such as personal protective equipment, hand sanitizer] and acquire extra cooking training, including food safety practices [34]. In Bangladesh, hospital authorities generally provide PPE to staff; however, the quality and adequacy of PPE can be a concern, especially during the crisis period [56]. A recent study reported that nearly half of the respondents [50%] claimed that there was an inadequate supply of PPE for hospitals and healthcare workers [56].…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, hospital authorities generally provide PPE to staff; however, the quality and adequacy of PPE can be a concern, especially during the crisis period [56]. A recent study reported that nearly half of the respondents [50%] claimed that there was an inadequate supply of PPE for hospitals and healthcare workers [56]. Hence, financial solvency enables them to carry hygienic materials for their own use regardless of their workplace.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, perceptions of protection and well-being varied widely among different HCW cadres. It is therefore important to implement targeted interventions based on the level of risk exposure of HCWs, rather than one-size-fits-all interventions [ 47 ]. These findings are consistent with finding from studies conducted in different settings in Africa, India and Iran, which have reported that different cadres of HCWs experience different levels of post-traumatic stress symptoms depending on their level of exposure [ 14 , 15 , 17 , 18 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their responsibility was challenging due to the limited healthcare infrastructure 15 . There were problems at the healthcare facilities, and HCWs faced difficulties in getting the necessary equipment to deal with the situation, such as Personal Protective Equipment (PPE) 16 and necessary training 17 . Very few stakeholders had thought of the HCWs' physical and mental health support 18 , whose families were also at risk 19 , and at some point, society was against them 19 .…”
Section: Coronavirusmentioning
confidence: 99%